A Global Analysis of Photoreceptor-Mediated Transcriptional Changes Reveals the Intricate Relationship Between Central Metabolism and DNA Repair in the Filamentous Fungus Trichoderma atroviride - Pola-Sánchez, Enrique; Villalobos-Escobedo, José Manuel; Carreras-Villaseñor, Nohemí; Martínez-Hernández, Pedro; Beltrán-Hernández, Emma Beatriz; Esquivel-Naranjo, Edgardo Ulises; Herrera-Estrella, Alfredo (Frontiers in Microbiology, 2021)
Light provides critical information for the behavior and development of basically all organisms. Filamentous fungi sense blue light through a unique transcription factor complex that activates its targets in a light-dependent manner. In Trichoderma atroviride, the BLR-1 and BLR-2 proteins constitute this complex, which triggers the light-dependent formation of asexual reproduction structures (conidia). We generated an ENVOY photoreceptor mutant and performed RNA-seq analyses in the mutants of this gene and in those of the BLR-1, CRY-1 and CRY-DASH photoreceptors in response to a pulse of low intensity blue light. Like in other filamentous fungi BLR-1 appears to play a central role in the regulation of blue-light responses. Phenotypic characterization of the Δenv-1 mutant showed that ENVOY functions as a growth and conidiation checkpoint, preventing exacerbated light responses. Similarly, we observed that CRY-1 and CRY-DASH contribute to the typical light-induced conidiation response. In the Δenv-1 mutant, we observed, at the transcriptomic level, a general induction of DNA metabolic processes and strong repression of central metabolism. An analysis of the expression level of DNA repair genes showed that they increase their expression in the absence of env-1. Consistently, photoreactivation experiments showed that Δenv-1 had increased DNA repair capacity. Our results indicate that light perception in T. atroviride is far more complex than originally thought.